Clinical profile of palmoplantar dermatoses in patients attending tertiary health center in central India - Rathoriya, Shyam Govind (International Journal of Research in Dermatology, 2018)
Background: Palmoplantar dermatoses include specific skin diseases affecting palm and soles and are frequently encountered dermatoses in the dermatology practice. Apart from diagnostic difficulties, few palmoplanter dermatoses cause great discomfort and disability and may also affect a person’s livelihood. Methods: It was a cross sectional descriptive study conducted in the Department of Dermatology, Chirayu Medical College and Hospital, Bhopal. A total of 200 patients of palmoplanter dermatoses, attending outpatient department of dermatology of tertiary health center were enrolled for study. Results: In our study, a total of 200 patients were included in the study, of which 116 (58.0%) were males and 84 (42.0%) were females. Male to female ratio was 1.38 showing male preponderance of disease. The most common age group affected was 31–40 years followed by 21–30 years in both the sexes. In our study, only palms were involved in 30 (15%) cases, soles in 39 (19.5%), and both palms and soles in 131 (65.5%) cases. Out of all palmoplanter dermatoses, 161 (80.5%) cases had palms and 170 (85%) cases had soles involvement. Palmoplantar psoriasis was the most common dermatoses found in 48 (24.0%) cases followed by palmoplanter keratoderma in 26 (13.0%). Conclusions: Early recognition of clinical symptoms and signs is important to plan further supportive diagnostic investigations as well as appropriate and effective management to further improve outcome of illness and the quality of life.